Aging and depression vulnerability interaction results in decreased serotonin innervation associated with reduced BDNF levels in hippocampus of rats bred for learned helplessness - Aznar, Susana; Klein, Anders B.; Santini, Martin A.; Knudsen, Gitte M.; Henn, Fritz A.; Gass, Peter; Vollmayr, Barbara (Synapse, 2010)
Epidemiological studies have revealed a strong genetic contribution to the risk for depression. Both reduced hippocampal serotonin neurotransmission and brain-derived neurotrophic factor (BDNF) levels have been associated with increased depression vulnerability and are also regulated during aging. Brains from young (5 months old) and old (13 months old) congenital Learned Helplessness rats (cLH), and congenital Non Learned Helplessness rats (cNLH) were immunohistochemically stained for the serotonin transporter and subsequently stereologically quantified for estimating hippocampal serotonin fiber density. Hippocampal BDNF protein levels were measured by ELISA. An exacerbated age-related loss of serotonin fiber density specific for the CA1 area was observed in the cLH animals, whereas reduced hippocampal BDNF levels were seen in young and old cLH when compared with age-matched cNLH controls. These observations indicate that aging should be taken into account when studying the neurobiological factors behind the vulnerability for depression and that understanding the effect of aging on genetically predisposed individuals may contribute to a better understanding of the pathophysiology behind depression, particularly in the elderly.